حدود و قصاص کے مقدمات میں تزکیۃ الشھود کی اہمیت اورضابطہ کار : Importance and regulation of Tazkiyyah al-Shud in the cases of Hudud and Qisas - Abdul Qadeer; Dr. Hafiz Muhammad Saleem (International Research Journal of Arabic and Islamic Studies, 2024)
Islamic judicial system based upon law of evidence. According to nature of relevant offences creditability and number of witnesses has been determined and fixed. Only evidence of creditable (Adel) witnesses is relied upon and Qazi is bond to reliance of evidence of credible witnesses only. Credible witnesses are those who abstain from major sins (gunah_e_kabeerah) and who avoid to repeat tiny (minor) sins. Holding of inquiry by court about credibility of witnesses is known as Tazkia_tul_sahood in Islamic terminology, it extend to case of every nature particularly and specifically it is mandatory in case of hadood and qisas and having legally, morally and ethically importance. The inquiry take start by issuing letter (Masturah) to person (Muzakki) who has adverse knowledge about concerned witnesses by court. The report submitted by person about the credibility of witnesses is known as Tazki report. In this article to elaborate the matter through inductively and deductively mode in the light of previously research, which will become helpful as procedural law to complete the proceeding of Tazkia-tul-sahood by court.